5-Selenocyanato and 5-trifluoromethanesulfonyl derivatives of 2′-deoxyuridine: synthesis, radiation and computational chemistry as well as cytotoxicity. Issue 38 (12th June 2018) - Makurat, Samanta; Zdrowowicz, Magdalena; Chomicz-Mańka, Lidia; Kozak, Witold; Serdiuk, Illia E.; Wityk, Paweł; Kawecka, Alicja; Sosnowska, Marta; Rak, Janusz
Abstract : Two 5-substituted-2′-deoxyuridine derivatives, SeCNdU and OTfdU, have been obtained and evaluated for their radiosensitizing potential. Abstract : 5-Selenocyanato-2′-deoxyuridine (SeCNdU) and 5-trifluoromethanesulfonyl-2′-deoxyuridine (OTfdU) have been synthesized and their structures have been confirmed with NMR and MS methods. Both compounds undergo dissociative electron attachment (DEA) when irradiated with X-rays in an aqueous solution containing a hydroxyl radical scavenger. The DEA yield of SeCNdU significantly exceeds that of 5-bromo-2′-deoxyuridine (BrdU), remaining in good agreement with the computationally revealed profile of electron-induced degradation. The radiolysis products indicate, in line with theoretical predictions, Se–CN bond dissociation as the main reaction channel. On the other hand, the DEA yield for OTfdU is slightly lower than the degradation yield measured for BrdU, despite the fact that the calculated driving force for the electron-induced OTfdU dissociation substantially overpasses the thermodynamic stimulus for BrdU degradation. Moreover, the calculated DEA profile suggests that the electron attachment induced formation of 5-hydroxy-2′-deoxyuridine (OHdU) from OTfdU, while 2′-deoxyuridine (dU) is mainly observed experimentally. We explained this discrepancy in terms of the increased acidity of OTfdU resulting in efficient deprotonation of the N3 atom, which brings about the domination of the OTfdU(N3–H) − anion in the equilibrium mixture. As a consequence, electron addition chiefly leads to the radical dianion, OTfdU(N3–H)˙ 2−, which easily protonates at the C5 site. As a result, the C5–O rather than O–S bond undergoes dissociation, leading to dU, observed experimentally. A negligible cytotoxicity of the studied compounds toward the MCF-7 cell line at the concentrations used for cell labelling calls for further studies aiming at the clinical use of the proposed derivatives.